Prayer Movement Material and Its Effect on PAI Learning Outcomes (Case Study at SMP Negeri 2 Simeulue Timur) - Adi Saleh; A’zizah A’zizah; Wolly Mistiar; Evi Mulyama (Budapest International Research and Critics University, 2022)
The competency base of Islamic subjects developed at SMPN 2 Simeulue Timur is directed at the growth of faith and piety to Allah SWT, mastery of academic abilities, arts and complete personality development. This research includes the type of quantitative research, In accordance with the type of research, this research uses a quantitative approach. The data analysis technique used is the analysis of